Burden of disease – the Australian experience. (19th October 2011) - Fritschi, Lin; Driscoll, Tim; Fernandez, Renae; Vallence, Deborah; Reid, Alison; Benke, Geza; Glass, Deborah
Abstract : Objectives: In 2006, we published estimates of the number of cancers caused by occupation in Australia. The aim was to raise the profile of occupational cancer among policy makers and practitioners. Methods: We estimated the number of cancers caused by occupation in Australia by applying Finnish estimates of the proportion of cancers caused by occupation to the Australian numbers of cancers. Results: We estimated that around 5000 invasive cancers and 34 000 non-melanoma skin cancers per year were caused by occupational exposures. There were many uncertainties in the available data and several major assumptions needed to be made so we warned that the estimates should be treated with caution. The estimates received some criticism from peers, but nevertheless they received considerable press coverage and stimulated a number of initiatives in Australia to address the issue of occupational cancer. To obtain better data for policy making we need to improve the data on prevalence of exposure, level of exposure and relative risk. As a first step to improving the estimates we developed a list of 38 priority carcinogens for which we are now obtaining data on prevalence and level of exposure. Conclusions: It is extremely difficult to obtain valid data to estimate burden of disease. However, the interest in the topic is quite high and policy makers and practitioners do seem to be receptive to advice on how to focus preventive activities such as exposure standard setting, enforcement and implementation of bans on the importation or use of the listed agents.